A blurred signal? The usefulness of National Senior Certificate (NSC) Mathematics marks as predictors of academic performance at university level - Schöer, Volker; Ntuli, Miracle; Rankin, Neil; Sebastiao, Claire; Hunt, Karin (Faculty of Education, University of the Free State, 2010)
Internationally, performance in school Mathematics has been found to be a reliable predictor of performance in commerce courses at university level. Based on the predictive power of school-leaving marks, universities use results from school-leaving Mathematics examinations to rank student applicants according to their predicted abilities. However, in 2008 the structure and scope of school-leaving examinations changed in South Africa from the former Senior Certificate (SC) to the new National Senior Certificate (NSC). This structural break seems to create fluctuations in the signalling ability of the schoolleaving marks. South African universities are unsure about how well the current NSC Mathematics marks reflect the underlying numerical competence of students, given that a high number of the 2009 student intake failed their first-year core courses across faculties. This paper estimates a deflator for the new NSC Mathematics marks relative to the former Higher Grade (HG) Mathematics marks, by comparing performance in similar first tests of two commerce subjects, Economics 1 and Computational Mathematics, between the 2008 and 2009 first-year cohorts. The results indicate that the signalling ability of the NSC Mathematics marks is reduced significantly. Instead of differentiating students according to their abilities, the new NSC Mathematics marks compress students with a wide range of abilities and disabilities into a very narrow range of percentage marks.
Keywords: University admission; First-year commerce courses; Matric mathematics; National Senior Certificate; Academic ability; Ability signalling